Atypical presentation of type A aortic dissection: a case report - Kostova, Nela; Otljanska, M; Kostov, I (My University, 2015)
Background: Aortic dissection typically presents with severe chest or back pain. Lower limb ischemia occurs in less than 10 % of cases of type A aortic dissection. Isolated distal limb ischemia as the first sign of dissection is very rare.1-3 Case report: A 75-year-old man with history of uncontrolled hypertension and smoking was admitted to our hospital with sudden onset of lower extremities pain. During exertion patient felt transient mild chest pain. He was asymptomatic few hours till onset of sharp pain in his left leg. He was admitted in our hospital with persisting symptoms and sings of critical distal limb ischemia. There was significant systolic blood pressure difference. Troponin T was negative, but other cardiac biomarkers were highly elevated. Transthoracic echocardiography detected aortic root dilatation, mild regurgitation and aortic arch intimal flap. CT angiography was performed and type A aortic dissection, with doubled lumen was detected from ascending aorta to aortic bifurcation. Supra-aortic vessels were not involved and no repercussion on celiac, renal or mesenteric artery flow was detected. Thrombus in left iliac artery with involvement of left external iliac artery could explain signs of distal limb ischemia. Patient was referred to cardiovascular center but unfortunately he died immediately after transfer to surgical institution. Discussion and Conclusions: Aortic dissection is an emergency that, unless it is quickly identified, almost regularly results in death, especially in presence of atypical or rare symptoms. Suddenonset of lower limb pain or signs of critical ischemia could be the signs of acute aortic disease and should be carefully investigated.
Keywords: aortic dissection